Joint Effects of Physical Activity and BMI on Risk of Hypertension in Women: A Longitudinal Study. (23rd January 2014) - Jackson, Caroline; Herber-Gast, Gerrie-Cor; Brown, Wendy
Abstract : Introduction . There is debate as to whether physical activity counteracts the adverse effect of weight on health outcomes. We investigated how physical activity modifies the effect of body mass index (BMI) on hypertension risk. Methods . BMI, physical activity, and hypertension were measured at baseline and at three-year interval for 14 years (from 1996 to 2010), in 10, 339 participants in the Australian Longitudinal Study on Women's Health. Generalised estimating equation models for binary repeated measures were performed to determine the individual and joint effects of BMI and physical activity on incident hypertension. Results . At baseline (mean age47.6 ± 1.5 SD), 57% were healthy weight, 28% overweight, and 14% obese. Increasing BMI and decreasing physical activity were associated with increased risk of hypertension. Physical activity attenuated the positive association between weight and risk of hypertension, especially for obese women. Compared to healthy weight high active women, risk of hypertension in obese high active women was 3.4 times greater (OR 3.43, 95% CI 2.68, 4.39) and in obese inactive women 4.9 times greater (OR 4.91, 95% CI 3.92, 6.13). Conclusions . Both physical activity and maintenance of a healthy body weight are associated with lower risk of hypertension. Physical activity reduced but did not remove the effect of obesity on hypertension risk.